Electrochemical activation construction of LaCo1-x-yNixFeyO3 promoted by optimized lattice Ni doping toward water oxidation. (29th November 2022) - Yu, Ning; Zhang, Xin-Yu; Wang, Qiu-Yue; Liu, Hai-Jun; Han, Guanqun; Wang, Feng-Ge; Zhou, Yu-Lu; Chai, Yong-Ming; Dong, Bin
Abstract: Iron sites with high intrinsic activity for oxygen evolution reaction (OER) can effectively enhanced the performance of perovskite oxide as electrocatalyst for water electrolysis. However, doping of iron in perovskite LaCoO3 remains a challenge owing the strong Co–O bond and robust structure of LaCoO3 . Herein, the lattice doping of Ni in LaCoO3 has been adopted to promote the interaction between iron ions and Co site in LaCoO3 . Firstly, molten salt of Ni(NO3 )2 provides free-moving Ni ions to substitute Co sites in the lattice of LaCoO3 forming LaCo1-x Nix O3 at the optimized Ni doping condition. Then, iron ions can easily be absorbed to LaCo1-x Nix O3 due to the strong interaction between Ni and Fe by electrochemical activation at room temperature. The prepared LaCo1-x-y Nix Fey O3 nanoparticles keep the coarse surface for maximizing the exposure of active sites. The high-valence Co and oxygen vacancy from LaCo1-x-y Nix Fey O3 contribute to the better intrinsic activity for OER, demonstrating the overpotential of ƞ10 of approximately 315 mV and good stability. The strategy of by introducing the lattice doping of other metal ion can realize the facile and effective construction of iron doped perovskite oxide for water oxidation. Graphical abstract: Image 1 Highlights: Molten salt of Ni(NO3 )2 provides Ni ions to substitute Co sites in the lattice of LaCoO3 . Iron ions are absorbed to LaCo1-x Nix O3 with the strong interaction Ni–Fe by electrochemical activation. Ni/Fe doping can expose more active site sites and adjust the electronic structure of Co sites. LaCo1-x-y Nix Fey O3 exhibits the motivated OER activity and stability.